PENYELIDIKAN POLA ALIRAN EMBUNG SAMIRAN DENGAN UJI MODEL HIDROLIK FISIK - Dyah Ari Wulandari; Kirno Kirno (Diponegoro University, 2010)
Samiran Dam is located in Grawah river, Boyolali Regency, Central Java Province. The aim of Samiran Damis for service water supply. The hydraulic model test are conducted for clarifying the appropriateness ofhydraulic design, to perfect and optimize the hydraulic design of the spillway. One of the main objective is tostudy the flow pattern approaching spillway, at spillway, stilling bazin and river in the downstream of thestilling bazin.The detail model is made as three dimensional model, covering the part of reservoir, spillway, stilling bazin andriver in the downstream of spillway. The hydraulic model test was carried out in The Hydraulic Laboratory ofExperimental Station for River in Surakarta.Base on the study result then there are necessary to modified design of the stilling bazin and to add groundsillconstruction at the river in the downstream of the stilling bazin